Intensive low-glycaemic-load dietary intervention for the management of glycaemia and serum lipids among women with gestational diabetes: a randomized control trial. Issue 8 (15th September 2014) - Ma, Wen-Jun; Huang, Zhi-Hong; Huang, Bi-Xia; Qi, Ben-Hua; Zhang, Yan-Jun; Xiao, Ben-Xi; Li, Yuan-Hong; Chen, Li; Zhu, Hui-Lian
Abstract: Objective: The present study aimed to compare the effects of a general dietary intervention and an intervention with low glycaemic load (GL) on glycaemic control, blood lipid metabolism and pregnancy outcomes in women with gestational diabetes mellitus. Design: Participants were randomly assigned to two groups, receiving either an individualized general dietary intervention (Control group) or an intensive low-GL intervention (Low-GL group) every two weeks, from 24–26 weeks of gestation to delivery. Setting: The Center of Maternal Primary Care in Guangdong General Hospital, China. Subjects: Ninety-five women with gestational diabetes mellitus were enrolled from June 2008 to July 2009. Results: After the intervention, both groups significantly decreased their dietary intakes of energy, fat and carbohydrate. The Low-GL group had significantly lower values for GL (122 v . 136) and glycaemic index (50 v . 54) but greater dietary fibre intake (33 v . 29 g/d) than did the Control group (all P <0·01). Significantly greater decreases in fasting plasma glucose (−0·33 v . −0·02 mmol/l, P <0·01) and 2 h postprandial glucose (−2·98 v . −2·51 mmol/l, P <0·01), significantly lower increases in total cholesterol (0·12 v . 0·23 mmol/l) and TAG (0·41 v . 0·56 mmol/l) and a significantly lower decrease in HDL cholesterol (−0·01 v . −0·11 mmol/l) were also observed in the Low-GL group compared with the Control group (all P <0·05). There were no significant differences in body weight gain, birth weight or other maternal–fetal perinatal outcomes between the two groups. Conclusions: The low-GL targeted dietary intervention outperformed the general dietary intervention in glycaemic control and the improvement of blood lipid levels in women with gestational diabetes mellitus.